554 Koolan Syndrome is a Novel Genomic Disorder with Mental Handicap Multiple Congenital Anomaly Due to Micro Deletion at 17Q21.31. (October 2012) - Ismail, AM; Mahony, MJ; Murphy, AM; Oreadon, W
Abstract : Aim: Our aim is to report a case of koolan syndrome in a 3 year old male child. Methods: Clinical history, physical examination, clinical photography results of molecular genetic testing are presented. Results: A male infant was born to a healthy Irish Caucasian non consangnious couple by normal vaginal delivery at 38 weeks gestation, Birth weight 2.3 kgs, and head circumference 33.5cms. It was his mothers third pregnancy. The first was a molar pregnancy. Second resulted in a birth of an Edward's syndrome who died at 3 weeks of age. At birth he was hypotonic admitted to neonatal unit with low blood glucose of 1.6 mmol/L and on examination he has low set ears, long face widely spaced nipples narrow palpebral fissures and right undescended testis with feeding difficulty in neonatal period for which he required nasogastric feeds for first 3 weeks of life. With in last 3 years he is having global developmental delay pleasant behaviour and learning difficulties.